A continuous involvement of stakeholders promotes the ecosystem approach to fisheries in the 8-fjords area on the Swedish west coast. (23rd December 2016) - Bryhn, Andreas C.; Lundström, Karl; Johansson, Amelie; Ragnarsson Stabo, Henrik; Svedäng, Henrik
Abstract : The coastal marine environment in the 8-fjords area on the Swedish west coast has been subjected to various stakeholder co-management initiatives since 1999. Stakeholders and authorities have acted by supporting and implementing gradually stricter fishing restrictions following the collapse in the 1970s of several demersal fish stocks and their apparent lack of recovery. Moreover, concerns have been raised regarding a locally sharp depletion of eelgrass meadows, in addition to an apparent increase in the number of seals and cormorants. The present 8-fjords initiative applies a cross-sector approach to environmental management and thus also addresses various types of environmental pollution. This study has compared the environmental work around the 8-fjords to 15 principles regarding the ecosystem approach to fisheries (EAF). The main strength that has been identified among the EAF principles is the continuous involvement of stakeholders. Among weaknesses in the EAF is the scarcity of suitable indicators that are necessary for appropriate monitoring, especially biomasses of functional groups as well as economic and social indicators. Many environmental problems in the fjords remain and it is possible that improved adherence to EAF principles will facilitate solving some problems and alleviating others. Moreover, the application of the EAF in practice in the 8-fjords can serve as a guiding example for co-managing other aquatic ecosystems towards ecological, economic, and social sustainability. The experiences from the 8-fjords initiative, including its extensive stakeholder involvement, may serve as a practical EAF example to be studied by researchers and managers globally.